2015
DOI: 10.1016/j.ic.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Fast collaborative graph exploration

Abstract: We study the following scenario of online graph exploration. A team of k agents is initially located at a distinguished vertex r of an undirected graph. At every time step, each agent can traverse an edge of the graph. All vertices have unique identifiers, and upon entering a vertex, an agent obtains the list of identifiers of all its neighbors. We ask how many time steps are required to complete exploration, i.e., to make sure that every vertex has been visited by some agent.We consider two communication mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…One problem closely related to Dispersion is the graph exploration by mobile robots. The exploration problem has been heavily studied in the literature for specific as well as arbitrary graphs, e.g., [2,4,8,13,17]. It was shown that a robot can explore an anonymous graph using Θ(D log ∆)-bits memory; the runtime of the algorithm is O(∆ D+1 ) [13].…”
Section: Algorithm Memory Per Robot Time (In Rounds) (In Bits)mentioning
confidence: 99%
See 1 more Smart Citation
“…One problem closely related to Dispersion is the graph exploration by mobile robots. The exploration problem has been heavily studied in the literature for specific as well as arbitrary graphs, e.g., [2,4,8,13,17]. It was shown that a robot can explore an anonymous graph using Θ(D log ∆)-bits memory; the runtime of the algorithm is O(∆ D+1 ) [13].…”
Section: Algorithm Memory Per Robot Time (In Rounds) (In Bits)mentioning
confidence: 99%
“…Algorithm 1: Algorithm Graph Disperse(k) to solve Dispersion. 1 if i is alone at node then 2 i.settled ← 1; do not set i.treelabel 3 for pass = 1, log k do 4 Stage 1 (Graph DFS: for group dispersion of unsettled robots) 5 for round = 0, min(4m − 2n + 2, k∆) do 6 if visited node is free then 7 highest ID robot r settles; r.treelabel ← x.ID, where x is robot with lowest ID 8 x continues its DFS after r sets its parent, child for DFS of x reset parent, child, treelabel, mult, home // Lexico-priority: (mult, treelabel/ID). Higher mult is higher priority; if mult is equal, lower treelabel/ID has higher priority.…”
Section: Stagementioning
confidence: 99%
“…1. what parameters of the graph are known to the robots, 2. whether the graph is anonymous, 3. whether memory is allowed at robots [13], 4. whether memory is allowed at the nodes [7], 5. whether knowledge of the incoming ports through which a robot enters nodes is allowed [13], 6. whether exploration is by a single robot or cooperating robots [5], [6], [9], 7. if exploration is by multiple robots, whether robots are allowed to communicate under the local communication model or the global communication model [5], [6], [9], 8. if exploration is by multiple robots, whether robots are colocated or dispersed in the initial configuration, 9. whether we are designing a solution that is time optimal, or space optimal, 10. whether the bounds on memory are subject to time optimality solutions, 11. whether termination of the robot is required (and if so, whether at the starting node) or it is to perpetually traverse the graph…”
Section: Related Workmentioning
confidence: 99%
“…Thereafter, each traversal of the graph takes up to O(∆ 10 m) time steps. Dereniowski et al [9] studied the trade-off between graph exploration time and number of robots, assuming that (i) nodes have unique identifiers, (ii) when visiting a node, a list of all its neighbors is also known, (iii) all the robots are located at one node in the initial configuration, (iv) robots have unique identifiers, and (v) there is no bound on the memory of robots, which construct a map of the previously visited subgraph. The authors considered results in both the local communication model, as well as the global communication model.…”
Section: Related Workmentioning
confidence: 99%
“…However, optimization of the search by the use of multiple robots often involves coordination issues, where the searchers need to communicate in order to synchronize their efforts and adequately split the entire task into portions assigned to individual robots (cf. [13,23,25,27]). As this objective is often not easy to achieve, some multi-robot search problems turn out to be NP-hard (e.g., see [27]).…”
Section: Related Workmentioning
confidence: 99%